2021
DOI: 10.1136/gutjnl-2020-323263
|View full text |Cite
|
Sign up to set email alerts
|

Rapid gut dysbiosis induced by stroke exacerbates brain infarction in turn

Abstract: ObjectiveStroke is a leading cause of death and disability worldwide. Neuroprotective approaches have failed in clinical trials, thus warranting therapeutic innovations with alternative targets. The gut microbiota is an important contributor to many risk factors for stroke. However, the bidirectional interactions between stroke and gut microbiota remain largely unknown.DesignWe performed two clinical cohort studies to capture the gut dysbiosis dynamics after stroke and their relationship with stroke prognosis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
191
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 175 publications
(194 citation statements)
references
References 49 publications
3
191
0
Order By: Relevance
“…In terms of the composition of the gut microbiota, we were able to determine the bacterial taxa that most likely explain the differences between the SAP and non-SAP groups by applying the LEfSe algorithm, which has been validated for high-dimensional microbiome data sets. Some disease-promoting pathogens, such as Enterococcus ( Xia et al., 2019 ; Tan et al., 2020 ; Xu et al., 2021 ), overgrew in SAP subjects and were related to worse clinical outcomes in these patients. The integration of data regarding the most relevant taxa that characterized each patient group allowed us to calculate the MDI, which was significantly elevated in patients with SAP, especially in those with severe pneumonia, and related to systemic inflammation and immunosuppression, two important variables of SAP ( Hoffmann et al., 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In terms of the composition of the gut microbiota, we were able to determine the bacterial taxa that most likely explain the differences between the SAP and non-SAP groups by applying the LEfSe algorithm, which has been validated for high-dimensional microbiome data sets. Some disease-promoting pathogens, such as Enterococcus ( Xia et al., 2019 ; Tan et al., 2020 ; Xu et al., 2021 ), overgrew in SAP subjects and were related to worse clinical outcomes in these patients. The integration of data regarding the most relevant taxa that characterized each patient group allowed us to calculate the MDI, which was significantly elevated in patients with SAP, especially in those with severe pneumonia, and related to systemic inflammation and immunosuppression, two important variables of SAP ( Hoffmann et al., 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, clinical data concerning the association between the gut microbiota and SAP in China remain limited. We previously reported that disruption of the gut microbiota and its metabolites, including trimethylamine-N-oxide and SCFAs, are associated with stroke injury and outcome in AIS patients ( Xia et al., 2019 ; Tan et al., 2020 ; Xu et al., 2021 ). We further identified that an expansion of Enterobacteriaceae in the gut is an independent risk factor for poor functional outcome in AIS patients ( Xu et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gut microbiota from AD patients were transplanted into New mechanism of neuroinflammation in Alzheimer's disease: The activation of NLRP3 inflammasome mediated by gut microbiota Kim et al, 2020 Transfer of a healthy microbiota reduces amyloid and tau pathology in an Alzheimer's disease animal model Mezö et al, 2020 Different effects of constitutive and induced microbiota modulation on microglia in a mouse model of Alzheimer's disease Wang et al, 2020 The gut microbiota attenuate neuroinflammation in manganese exposure by inhibiting cerebral NLRP3 inflammasome Amelioration of AD pathology Bourassa et al, 2016 Butyrate, neuroepigenetics and the gut microbiome: Can a high fiber diet improve brain health? Bonfili et al, 2017 Microbiota modulation counteracts Alzheimer's disease progression influencing neuronal proteolysis and gut hormones plasma levels Bonfili et al, 2018 SLAB51 probiotic formulation activates SIRT1 pathway promoting antioxidant and neuroprotective effects in an AD mouse model Rezaeiasl et al, 2019 The effects of probiotic Lactobacillus and Bifidobacterium Strains on memory and learning behavior, long-term potentiation (LTP), and some biochemical parameters in β-amyloid-induced rat's model of Alzheimer's disease Lee et al, 2019 Suppression of gut dysbiosis by Bifidobacterium longum alleviates cognitive decline in 5XFAD transgenic and aged mice Mehrabadi and Sadr, 2020 Assessment of probiotics mixture on memory function, inflammation markers, and oxidative stress in an Alzheimer's disease model of rats Aggravation of stroke pathology Singh et al, 2016 Microbiota dysbiosis controls the neuroinflammatory response after stroke Yamashiro et al, 2017 Gut dysbiosis is associated with metabolism and systemic inflammation in patients with ischemic stroke Stanley et al, 2018 An insight into intestinal mucosal microbiota disruption after stroke Ahnstedt et al, 2020 Sex differences in T cell immune responses, gut permeability and outcome after ischemic stroke in aged mice Jeon et al, 2020 Dynamic changes in the gut microbiome at the acute stage of ischemic stroke in a pig model Xu et al, 2021 Rapid gut dysbiosis induced by stroke exacerbates brain infarction in turn Amelioration of stroke pathology Wang et al, 2011 Valproic acid attenuates blood-brain barrier disruption in a rat model of transient focal cerebral ischemia: the roles of HDAC and MMP-9 inhibition Hasan et al, 2013 Effect of HDAC inhibitors on neuroprotection and neurite outgrowth in primary rat cortical neurons following ischemic insult Kim and Chuang, 2014 HDAC inhibitors mitigate ischemia-induced oligodendrocyte damage: potential roles of oligodendrogenesis, VEGF, and anti-inflammation…”
Section: Microbiota and Alzheimer's Diseasementioning
confidence: 99%
“…Observation of a clinical cohort of patients with ischemic stroke revealed a fast induction of intestinal ischemia and an excessive production of nitrate resulting in gut dysbiosis with expansion of Enterobacteriaceae (Xu et al, 2021). Overgrowth of Enterobacteriaceae magnifies brain infarction by enhancing systemic inflammation and is a potential risk biomarker for a poor primary outcome of patients.…”
Section: Microbiota and Strokementioning
confidence: 99%